Interpreting Cultures - Hart, J. author. aut Link
XI, 340 p.
Keywords: This book focuses on how we perceive, know and interpret culture across disciplinary boundaries. The study combines theoretical and critical contexts for close readings in culture through discussions of literature, philosophy, history, psychology and visual arts by and about men and women in Europe, the Americas and beyond.